Risk factors for incident neck and shoulder pain in hospital nurses. Issue 11 (22nd October 2003) - Smedley, J; Inskip, H; Trevelyan, F; Buckle, P; Cooper, C; Coggon, D
Abstract : Aim: To assess the incidence and risk factors for neck and shoulder pain in nurses. Methods: A longitudinal study of neck and shoulder pain was carried out in female nurses at two hospitals in England. Personal and occupational risk factors were assessed at baseline. The self reported incidence of symptoms in the neck and shoulder region was ascertained at three-monthly intervals over two years. A Cox regression model was used to estimate hazard ratios (HRs) for incident neck/shoulder pain during follow up in nurses who had been pain free for at least one month at baseline. Results: The baseline response rate was 56%. Of 903 women who were pain free at baseline, 587 (65%) completed at least one follow up while still in the same job. During an average of 13 months, 34% of these (202 women) reported at least one episode of neck/shoulder pain. The strongest predictor of pain in the neck/shoulder was previous history of the symptom (HRs up to 3.3). For physical exposures at work, the highest risks (HRs up to 1.7) were associated with specific patient handling tasks that involved reaching, pushing, and pulling. Nurses who reported low mood or stress at baseline were more likely to develop neck/shoulder pain later (HR 1.5). Workplace psychosocial factors (including job demands, satisfaction, and control) were not associated with incident neck/shoulder symptoms. Conclusions: Neck/shoulder pain is common among hospital nurses, and patient handling tasks that involve reaching and pulling are the most important target for risk reduction strategies.